Genetic Diversity of Bali Cattle Based on Microsatellite Marker in Indonesian Breeding Centre - Wike andre Septian; . Jakaria; Cece Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2015)
Genetics characterization in livestock based on microsatellite has been widely implemented including for Bali cattle in three different breeding centres in Indonesia. This study aimed to determine diversity of Bali cattle microsatellites in three breeding centers namely BPTU Bali cattle in Bali, BPT-HMT Serading Sumbawa in West Nusa Tenggara, and Village Breeding Center in South Sulawesi. The number of animals used in this study was 95 head of cattle consisted of 32 heads from BPTU Bali Province, 32 heads from BPT-HMT Serading Sumbawa, and 31 heads from Village Barru Breeding Center Barru distric. Microsatellite loci used to determine the diversity was the locus SPS115, INRA037, MM12, and ETH185 based on flourescently labeled fragment method. Data analysis of microsatellite in Bali cattle at three different locations was performed by using POPGEN 1.2, Cervus, and POPTREE2 programs. The results showed that microsatellite diversity in Bali cattle detected 32 alleles from three different locations, and there were specific alleles at each location. Average values of observed heterozygosity (Ho) and expected heterozygosity (He) were 0.418 and 0.604 respectively, while the average value of polymorphism informative content (PIC) was 0.579. The Hardy-Weinberg equilibrium in general suggested that the loci used in the Bali cattle in three populations were in equilibrium, except INRA037 and ETH185. The genetic diversity between populations of Bali cattle was 0.033 (3%), while the inbreeding coefficient index in all populations was 0.296 (29.6 %). Bali cattle phylogeny tree with three populations showed that the populations of Bali cattle in BPTU Bali and VBC Barru had close genetic distance compared to the population of Bali cattle in BPT-HMT Serading Sumbawa. The results of this study provide information that the characteristics of Bali cattle breeding centers in three locations are different, so we need a directed breeding program in each population.Key words: Bali cattle, genetics diversity, microsatellite